Docker, Dockerfile, and Docker-Compose (2020 Ready!) - Wiesner, Thomas (Packt Publishing, 2020)
Get to grips with Docker, containers versus images, and more by learning through a hands-on approach About This Video Explore the process of installing Docker on Windows Professional or Server (with Hyper-V) Become well-versed with running a single Docker Container as well as multiple Docker Containers Understand how to use and define network segregation in Docker and the Docker0 network In Detail If you have never worked with containerization before or you need a quick refresher on the most common commands and patterns using Docker, then this course is for you. Although there are other containerization frameworks or tools, Docker has emerged as the standard when it comes to using it for everything from developers' machines to production-ready cloud deployments. In this course, you will learn how to use Docker in your daily development workflow from the very start to increase your productivity. You'll discover Docker Run, before going on to understand how to read, understand, and write docker-compose.yml files. As you progress, the course will take you through developing Docker images, along with helping you understand the technique of creating a custom configuration with Dockerfile. Later, you will explore the benefits of a local development environment versus virtual machines versus Docker. By the end of this course, you will be well-versed with Docker, and have developed the skills you need to use it effectively to manage your environment.
Online resource; Title from title screen (viewed January 31, 2020)
Keywords: Electronic videos